1986
DOI: 10.1126/science.3083507
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Macrophage Tumoricidal Activity by Granulocyte-Macrophage Colony-Stimulating Factor

Abstract: Monocytes are a subpopulation of peripheral blood leukocytes, which when appropriately activated by the regulatory hormones of the immune system, are capable of becoming macrophages--potent effector cells for immune response to tumors and parasites. A complementary DNA for the T lymphocyte-derived lymphokine, granulocyte-macrophage colony-stimulating factor (GM-CSF), has been cloned, and recombinant GM-CSF protein has been expressed in yeast and purified to homogeneity. This purified human recombinant GM-CSF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
172
0
3

Year Published

1987
1987
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(182 citation statements)
references
References 34 publications
7
172
0
3
Order By: Relevance
“…In particular, GM-CSF promotes antibody-dependent cellular cytotoxicity (ADCC) of neutrophils [9] and mononuclear cells [10], increases expression of adhesion molecules on granulocytes and monocytes [11,12] and enhances the antigen-presenting ability of monocytes [13]. These properties suggest that GM-CSF alone [14][15][16] or used in combination therapy may be beneficial in inducing or augmenting tumour regression [17].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, GM-CSF promotes antibody-dependent cellular cytotoxicity (ADCC) of neutrophils [9] and mononuclear cells [10], increases expression of adhesion molecules on granulocytes and monocytes [11,12] and enhances the antigen-presenting ability of monocytes [13]. These properties suggest that GM-CSF alone [14][15][16] or used in combination therapy may be beneficial in inducing or augmenting tumour regression [17].…”
Section: Introductionmentioning
confidence: 99%
“…32,33 GM-CSF released by antigenspecific T cells which reach the tumor site may either potentiate the effect of concomitant produced IFN␄ and other secondary cytokines, and recruit and activate macrophages and granulocytes that are associated with tumor killing through nonspecific bystander effects. 6,34,35 In addition, we showed that GM-CSF can substitute for IFN␄ in inducing rejection of C26/IL-12 injected into IFN␄ KO mice. 36 IL-12 has also been reported to modulate immunodominance of cytotoxic T lymphocytes epitopes coinjected in vivo.…”
Section: Discussionmentioning
confidence: 80%
“…While several studies have shown GM-CSF to be able to prime monocytes by enhancing the release of superoxide, 38 or by stimulating accessory cell function (transcriptional regulation of HLA-DR and IL-1 expression), 39 the role of GM-CSF in enhancing cytotoxicity is still controversial. 40,41 Furthermore, it is still not clear whether GM-CSF activation of monocytes requires a second signal as proposed by Cannistra et al 42 and Hart et al 43 or discussed for IFN-␄. 44 Several groups have shown that combined treatment with GM-CSF and IFN-␄ led to a synergistic tumoricidal activity.…”
Section: Figure 6 Residual Colonies Of U-937 After 2 Weeks Of Cocultumentioning
confidence: 99%